(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article, some comments are made about the pedagogical conditions of using methodical games in the teaching of a second language in the preschool education system and its importance in today’s pedagogical system. Also, the article gives examples of some methodical games and describes the processes of their implementation.